Use of Base Catalysts in Making Biodiesel from Waste Cooking Oil - Syafitri, Dwi; Putri Arza, Tasya Dwi Putri Arza; Rusdianasari, Rusdianasari (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Biodiesel obtained from vegetable oils and animal fats, is a more environmentally friendly alternative to conventional fossil fuels. Biodiesel production through esterification and transesterification processes with an emphasis on the role of catalysts in increasing efficiency. The use of homogeneous and heterogeneous catalysts, as well as the advantages and disadvantages of each. Homogeneous catalysts, such as NaOH and KOH, are effective in increasing the reaction, but face challenges in product separation and soap formation that can reduce biodiesel yields. In contrast, heterogeneous catalysts such as CaO and zeolites offer advantages in terms of reuse and waste reduction, although with slightly lower efficiency. In addition, important factors such as catalyst concentration, alcohol to oil ratio, and reaction temperature are also reviewed to maximize biodiesel yields. Optimal catalyst concentration is essential to increase conversion efficiency, as inappropriate concentrations can slow down the reaction. The importance of choosing the right catalyst and process conditions in producing biodiesel efficiently, while considering the environmental impact of using raw materials, especially palm oilContribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 11: Sustainable Cities and CommunitiesSDG 13: Climate ActionSDG 15: Life on Land